L'efficacité d'une stratégie d'intervention émotivo-rationnelle auprès d'adolescents dépressifs du millieu scolaire - Marcotte, Diane; Baron, Pierre (Canadian Journal of Counselling and Psychotherapy, 1993)
This school-based study verifies the efficacy of a group rational-emotive intervention with depressive teenagers. Twenty-five teenagers, aged 14 to 17 years, took part in this study. Following a selecting procedure inspired by Reynolds ( 1986), the subjects were assigned to two experimental groups and to two waiting list control groups. Twelve meetings were offered to the experimental groups according to Bernard and Joyce's program (1984). Data were collected from pre-test, post-test, and follow-up. The measurements used for the depression were Beck Depression Inventory, the Hamilton Depression Rating Scale, and an observational questionnaire by the teachers. Kassinove and Berger's Survey of Personal Beliefs was used as a measurement of irrational thinking. The results at the post-test show a diminution of the level of depression in both the experimental groups and the control groups, but was kept only for the experimental groups at the follow-up. With the subjects of the same gorups, a diminution of the level of irrational beliefs, which stays present at the follow-up, is observed at the post-test. The results are discussed with the current development of intervention strategies for the treatment of depression in teenagers.